PENGARUH VARIABEL MAKRO EKONOMI DAN PENYALURAN ZAKAT, INFAK, DAN SEDEKAH OLEH BADAN AMIL ZAKAT NASIONAL TERHADAP KEMISKINAN DI INDONESIA - Jasmine Fitri Andrini; Ilmiawan Auwalin (Universitas Airlangga, 2019)
This research aims to know the effect of macroeconomics variable, such as Gross Domestic Product (GDP), unemployment, inflation, and gini ratio and distribution of Zakat, Infaq, and Sodaqoh (ZIS) from National Zakat Agency against poverty in Indonesia during 2007 to 2017 simultaneously and partially in long run and short run. This study used vector error correction model technique. The result of this research indicates that GDP, inflation, gini ratio, and distribution of ZIS partially have a negative and significant effect to poverty in long run. Meanwhile, unemployment partially has a positive and significant effect to poverty in long run. In short run, GDP, inflation and distribution of ZIS partially have a negative and not significant effect to poverty, unemployment has a positive insignificant effect to poverty. Meanwhile, gini ratio partially has a significant and negative effect to poverty. Simultaneoosly, all variables affect poverty.Keywords: Gross Domestic Product (GDP), Unemployment, Inflation, Gini ratio, Zakat Infaq Sodaqoh (ZIS), Poverty